Sistemas espaciais de navega??o e o impacto do efeito doppler no geolocal - Sabsud, Marcelo Cesarino Chahud (2008)
The purpose of this work is to study the possible error sources caused by the Doppler effect in the geopositioning system ?Geolocal? and to suggest solutions for their correction by carrying out mathematical analyses of physical models and laboratory experiments for the solution of the problems. The work presents the "Geolocal" system and other location systems using space techniques, GNSS (Global Navigation Satellite Systems). For this purpose, considerations and mathematical tools were developed to determine the Doppler effects on the Geolocal system, resulting in numerical values of frequency for several proposed conditions of mathematical simulation. Initially it was shown that the Doppler effect does not influence directly the measurement of the time-propagation difference of the signals carrying information of the instants of reference. However, it can produce variation in the instrumental phase delays in the circuits used to correct the Doppler frequency shifts. The results obtained by the simulations produced data used in laboratory tests, providing measurements of time-variations caused by the demodulation of the received signal with and without the AFC (Automatic Frequency Control). It was possible to show that the phase shifts caused by the electronic circuits to correct the frequency shifts due to Doppler effect, are minimized to bring them to sufficiently low values that do not influence the system.